2016
DOI: 10.4048/jbc.2016.19.4.429
|View full text |Cite
|
Sign up to set email alerts
|

Detectability and Usefulness of Automated Whole Breast Ultrasound in Patients with Suspicious Microcalcifications on Mammography: Comparison with Handheld Breast Ultrasound

Abstract: PurposeThe purpose of this study was to prospectively evaluate the detectability and usefulness of automated whole breast ultrasound (AWUS) and to compare it with handheld breast ultrasound (HHUS) in cases with suspicious microcalcifications identified by mammography.MethodsForty-two patients with 43 suspicious microcalcifications (25 malignant and 18 benign) detected by mammography underwent AWUS, HHUS, and histol-ogic examination. With knowledge of the mammographic findings, HHUS was performed to assess the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…We then screened titles and abstracts to exclude 322 articles that did not meet the inclusion criteria or that met the exclusion criteria. We completely evaluated the remaining 82 articles, among which 17 (12 in English, 5 in Chinese) (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) were selected for diagnostic accuracy analysis and 13 (11 in English, 2 in Chinese) (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) were selected for detection rate analysis (Figure 1). Because 8 articles were used for both diagnostic accuracy and detection rate, a total of 22 articles (13-34) were included in this study (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…We then screened titles and abstracts to exclude 322 articles that did not meet the inclusion criteria or that met the exclusion criteria. We completely evaluated the remaining 82 articles, among which 17 (12 in English, 5 in Chinese) (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) were selected for diagnostic accuracy analysis and 13 (11 in English, 2 in Chinese) (22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34) were selected for detection rate analysis (Figure 1). Because 8 articles were used for both diagnostic accuracy and detection rate, a total of 22 articles (13-34) were included in this study (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…However, despite the small number of cases, we found that the MDTA imaging method may have less additional value when detecting amorphous calcifications, which have been reported to be difficult to detect with B-mode US as well 20 . The single case that showed a detection rate lower than 80% for consensus-positive cells presented as amorphous grouped microcalcifications on mammography, with a detection rate of 50% using MDTA imaging.…”
Section: Discussionmentioning
confidence: 53%
“…83.0% (477/575) were detected by AB US, which was higher than 74.4% in Choi et al’s study. Similarly, the detection rate of malignant calcification was significantly higher than that in benign lesions (88.7% vs. 78.1%) [ 18 ], which were displayed with architectural distortion, amorphous, coarse heterogeneous and fine pleomorphic morphology, and distributed with grouped, linear and segmental.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are few reports on the evaluation of microcalcifications by AB US. To our knowledge, only a prospective study by Choi et al reported that ABUS and HHUS have comparable detectability for suspicious calcification in a small sample (including 42 patients with 43 suspicious microcalcifications) [ 18 ]. The detection and diagnostic ability of AB US for breast microcalcification needs further exploration.…”
Section: Introductionmentioning
confidence: 99%